Policy divergence across crises of a similar nature: the role of ideas in shaping 19th century famine relief policies. Issue 3 (4th May 2021) - Curran, Declan; Mahmalat, Mounir
Abstract: This paper explores the phenomenon of policy divergence in response to crises of a similar nature. We argue that politically dominant interpretations of the nature of a crisis constitute a central mechanism that determines the shape of prevailing policy responses to that crisis. These interpretations lend legitimacy to views and policy proposals of certain political actors over others, which strengthens their position in the political bargain from which the eventual policy response emerges. As a consequence, political actors can exert a greater influence within the policy-making process even in the absence of a shift in the underlying institutional or political configuration of power. We illustrate this via a case study which explores two crisis episodes – the Great Irish Famine (1845–1850) and the Lancashire Cotton Famine (1861–1865) - in which one particular policy response was proposed by policymakers, yet the eventual legislative outcome differed significantly.